2003
DOI: 10.1177/0887302x0402100404
|View full text |Cite
|
Sign up to set email alerts
|

Concerns About Payment Security of Internet Purchases: A Perspective on Current On-Line Shoppers

Abstract: Consumers’ concerns about payment security have been recognized as an obstacle to the growth of Internet shopping. The purpose of our study was to investigate the influence of payment security concerns on Internet purchases. We proposed that consumers’ concerns about payment security mediate the relationship between attitude toward Internet shopping and actual purchases. Using data from the Georgia Institute of Technology Graphics Visualization and Usability Center’s 10th WWW User Survey, we found empirical ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…In other words, it refers to the ability of an individual to control, manage, and selectively reveal personal information (Eastick et al, 2006). Compared with shopping at physical stores, privacy/security concerns are a major barrier for purchasing online because online shopping brings a greater degree of uncertainty regarding interaction with websites/retailers and monetary transaction (Kwon and Lee, 2003). In the context of a social shopping website, privacy/security is associated with security of transactions, privacy of consumers' personal information, and guarantee of website safety.…”
Section: Privacy/securitymentioning
confidence: 99%
“…In other words, it refers to the ability of an individual to control, manage, and selectively reveal personal information (Eastick et al, 2006). Compared with shopping at physical stores, privacy/security concerns are a major barrier for purchasing online because online shopping brings a greater degree of uncertainty regarding interaction with websites/retailers and monetary transaction (Kwon and Lee, 2003). In the context of a social shopping website, privacy/security is associated with security of transactions, privacy of consumers' personal information, and guarantee of website safety.…”
Section: Privacy/securitymentioning
confidence: 99%
“…Commercial websites are designed by the good organization, ease of navigation, the lack Lutter, and quick access. Security Credit cards are the most dominant concern advent of electronic commerce (Kwon and Lee, 2003, Chain Store Age, 1999, Szymanski and Hise, 2000. Szymanski and Hise (2000) found that the level of economic consumers feel safe with online retailers related to e-satisfaction.…”
Section: Perceived Ease Of Use (Peou)mentioning
confidence: 99%
“…Moreover, it may be because, no item was inserted regarding the payment security in the proposed research model. According to Kwon and Lee (2003), 'intention' is influenced from the trust which is specifically related with the payment security.…”
Section: Discussionmentioning
confidence: 99%